LB0001 EFFICACY AND SAFETY OF UPADACITINIB VERSUS PLACEBO AND ADALIMUMAB IN PATIENTS WITH ACTIVE PSORIATIC ARTHRITIS AND INADEQUATE RESPONSE TO NON-BIOLOGIC DISEASE-MODIFYING ANTI-RHEUMATIC DRUGS (SELECT-PsA-1): A DOUBLE-BLIND, RANDOMIZED CONTROLLED PHASE 3 TRIAL. (13th June 2020) - Mcinnes, I.; Anderson, J.; Magrey, M.; Merola, J. F.; Liu, Y.; Kishimoto, M.; Jeka, S.; Pacheco Tena, C. F.; Wang, X.; Chen, L.; Zueger, P.; Pangan, A.; et al.
Abstract : Background: Upadacitinib (UPA) is an oral, reversible, JAK inhibitor approved for treatment of rheumatoid arthritis (RA) and currently under evaluation for treatment of psoriatic arthritis (PsA). Objectives: To assess the efficacy and safety of UPA vs placebo (PBO) and adalimumab (ADA) in patients (pts) with PsA and prior IR or intolerance to ≥1 non-biologic DMARD (non-bDMARD). Methods: Pts with active PsA (≥3 swollen and ≥3 tender joints), active or historical psoriasis, and on ≤2 non-bDMARDs were randomized 1:1:1:1 to once daily UPA 15 mg (UPA15), UPA 30 mg (UPA30), ADA 40 mg every other week, or PBO. The primary endpoint was the proportion of pts achieving ACR20 for UPA vs PBO at Wk 12. Multiplicity controlled secondary endpoints for each dose of UPA vs PBO included change in HAQ-DI, FACIT-F, and SF-36 PCS (Wk 12); static Investigator Global Assessment of Psoriasis of 0 or 1, PASI75, and change in Self-Assessment of Psoriasis Symptoms (Wk 16); change in modified Sharp/van der Heijde Score (mTSS), proportion of pts achieving MDA, and resolution of enthesitis (LEI=0) and dactylitis (LDI=0) (Wk 24). For each dose of UPA, the multiplicity-controlled analysis also included non-inferiority and superiority vs ADA for ACR20 and superiority for HAQ-DI and pt's assessment of pain NRS (Wk 12). ACR50/70 at Wk 12 and ACR20 at Wk 2 were additional secondary endpoints. Treatment-emergent adverse events (TEAEs) through 24 wks are reported for pts who received ≥1 dose of study drug. Results: 1705 pts were randomized; 1704 received study drug (53.2% female, mean age 50.8 yrs, mean duration of PsA diagnosis 6.1 yrs). 82% were on ≥1 concomitant non-bDMARD, of whom 84% received MTX +/- another non-bDMARD. At Wk 12, ACR20 rates were 70.6% with UPA15 and 78.5% with UPA30 vs 36.2% with PBO (p < .001 for UPA15/30 vs PBO) and 65.0% with ADA (non-inferiority, p < .001 for UPA15/30 vs ADA; superiority, p < .001 for UPA30 vs ADA). A greater proportion of pts achieved ACR50/70 with UPA15/30 vs PBO and UPA30 vs ADA. Improvements were observed with UPA15/30 vs PBO for all multiplicity controlled secondary endpoints and for UPA 15/30 vs ADA for HAQ-DI and UPA 30 vs ADA for improvement in pain (Figure 1A-1B ). At Wk 24, change in mTSS was 0.25 for PBO, -0.04 for UPA15, 0.03 for UPA30, and 0.01 for ADA (p < 0.001 for UPA15/30 vs PBO). The rates of TEAEs and serious AEs, including serious infections, were similar in the PBO, UPA15, and ADA arms and higher with UPA30 (Figure 2 ). The rate of herpes zoster was similar for PBO and UPA15/30. No MACE was reported with UPA. One malignancy occurred in each of the PBO and UPA15 arms, and 3 malignancies were reported in each of the UPA30 and ADA arms. VTE were reported in 1 pt on PBO, 1 pt on UPA30, and 2 pts on ADA. One death occurred in the PBO arm. Conclusion: In this non-bDMARD-IR PsA population, treatment with UPA15/30 demonstrated improvement in musculoskeletal symptoms, psoriasis, physical function, pain, and fatigue and inhibited radiographic progression; improvements were observed by Wk 2. At Wk 12, UPA15/30 were non-inferior to ADA for ACR20, with superiority demonstrated for UPA30. Greater percentages of UPA vs PBO pts achieved stringent measures of disease control (MDA, ACR50/70, sIGA 0/1). No new safety signals were identified compared with the safety profile observed in RA. Disclosure of Interests: Iain McInnes: None declared, Jaclyn Anderson Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., Marina Magrey Grant/research support from: Amgen, AbbVie, and UCB Pharma, Consultant of: Novartis, Eli Lilly, Pfizer, and Janssen, Joseph F. Merola Consultant of: Merck, Abbvie, Dermavant, Eli Lilly, Novartis, Janssen, UCB, Celgene, Sanofi, Regeneron, Arena, Sun Pharma, Biogen, Pfizer, EMD Sorono, Avotres and Leo Pharma, Yi Liu: None declared, Mitsumasa Kishimoto Consultant of: bbVie, Eli Lilly, Celgene, Pfizer, Gilead, Janssen, and UCB Pharma, Speakers bureau: AbbVie, Eisai, Celgene, Pfizer, Novartis, Eli Lilly, Tanabe-Mitsubishi, Ayumi, Janssen, Astellas, and UCB Pharma, Sławomir Jeka Speakers bureau: AbbVie, Pfizer, Roche, Novartis, MSD, Sandoz, Eli Lilly, Egis, UCB, Celgene, Cesar Francisco Pacheco Tena: None declared, xin wang Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., Liang Chen Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., Patrick Zueger Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., Aileen Pangan Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., Frank Behrens Grant/research support from: Pfizer, Janssen, Chugai, Celgene and Roche, Consultant of: Pfizer, AbbVie, Sanofi, Lilly, Novartis, UCB, Genzyme, Boehringer, Janssen, MSD, Celgene, Roche and Chugai